A Grammar of Khortha - Paudyal, Netra P., (Brill's Studies in South and Southwest Asian Languages ;, 2025)
Khortha is an Eastern Indo-Aryan language spoken in Jharkhand, India. Netra P. Paudyal provides an in-depth analysis of Khortha grammar based on the data recorded during his field trips, elicited data, and sentences culled from printed literature. Alongside, it includes a fully glossed text, a comparative wordlist of lexical items from three different varieties of this language and verb paradigms, making it of great interest and value to linguists and typologists. Additionally, it highlights Khortha's influence from Munda and other Indo-Aryan languages, with notable lexical borrowings, particularly from Santali. This comprehensive study makes a significant contribution to understanding the linguistic landscape of South Asia.